EVALUASI KEKRITISAN LAHAN DAERAH ALIRAN SUNGAI (DAS) DAN MENDESAKNYA LANGKAH-LANGKAH KONSERVASI AIR - Sarminingsih, Anik (Universitas Diponegoro, 2007)
There are some critical lands scattered in watershed or basin in Indonesia.The existing area that wide enough tend to threat the potential critical land which still good in other land uses, as: forest, plantation, cultivation, industry, mining, residential, etc. To prevent land degradation that increasing tends need effort for rehabilitating critical land. For potential critical land which still good enough needs prevent to watershed damage in order to watershed optimally functioned as producer and regular water. To obtain the aim was done by land conservation. Cisangkuy sub basin is apart of Citarum basin. Cisangkuy sub basin is a buffer zone in fulfilling water for Kotamadya Bandung and Kabupaten Bandung. Cisangkuy sub basin is critical which shown by erosion, sedimentation and discharge fluctuation. The erosion in Bandung valley specially in Cisangkuy sub basin is 163 ton/ha/yr. Sedimentation in Saguling reservoir is 3.02 – 4.32 billions m3 / year. Discharge fluctuation of minimum to maximum have range 49 - 394 m3/s. There are needed effort of land and water conservations by structural or non structural to suppor Gerakan Nasional - Kemitraan Penyelamatan Air (GNKPA)